Factors affecting emergency nurses' perceptions of the triage systems - Ani Sutriningsih; Chatarina Umbul Wahyuni; Setya Haksama (SAGE Publishing, 2020)
Background: Emergency services use a triage system to prioritize patients according to their level of diagnosis. Triage is one of the mandated skills to be owned by an emergency unit nurse. This research aims to identify factors affecting emergency nurses' perceptions of the triage systems. Design and Methods: 90 nurses were chosen based on quota sampling. Data were analyzed using Chi Square test (α=0.05) and logistic regression analysis. Results: The results show that nurses perceptions were influenced by knowledge (p=0.017), working experience (p=0.023), and training (p=0.041). The factor that had the strongest influence in the formation of nurses' perceptions was knowledge (p=0.020 and OR=3.19). Conclusions: It can be concluded that knowledge, working experience and training influenced emergency nurses' perceptions on triage systems.